Career, Family, and Workforce Mobility: An Interdisciplinary Conversation. (June 2020) - Patton, Wendy; Doherty, Catherine
The purpose of this article is to synthesize conceptual and empirical work from the fields of both sociology and career development to explore how issues of career, family, and workforce mobility are necessarily interrelated. The use of work from sociology and career development demonstrates that the complexities of family solutions to career mobility undo the apparent simplicity of delivering a worker to a new worksite. Although organizations and governments work to develop policies that incentivize mobility, including transport infrastructure, housing, employment conditions, and tax incentives, these will not necessarily address the private concerns and priorities of families. This article argues for an interdisciplinary approach to better understand the intersubjective complexities implicated in the growing phenomenon and expectation of worker mobility and suggests both areas and design strategies for further research.